SYNBIP: synthetic binding proteins for research, diagnosis and therapy. Issue Volume 50:Issue D1(2022) (19th October 2021) - Wang, Xiaona; Li, Fengcheng; Qiu, Wenqi; Xu, Binbin; Li, Yanlin; Lian, Xichen; Yu, Hongyan; Zhang, Zhao; Wang, Jianxin; Li, Zhaorong; Xue, Weiwei; Zhu, Feng
Abstract: The success of protein engineering and design has extensively expanded the protein space, which presents a promising strategy for creating next-generation proteins of diverse functions. Among these proteins, the synthetic binding proteins (SBPs) are smaller, more stable, less immunogenic, and better of tissue penetration than others, which make the SBP-related data attracting extensive interest from worldwide scientists. However, no database has been developed to systematically provide the valuable information of SBPs yet. In this study, a database named 'Synthetic Binding Proteins for Research, Diagnosis, and Therapy (SYNBIP)' was thus introduced. This database is unique in (a ) comprehensively describing thousands of SBPs from the perspectives of scaffolds, biophysical & functional properties, etc.; (b ) panoramically illustrating the binding targets & the broad application of each SBP and (c ) enabling a similarity search against the sequences of all SBPs and their binding targets. Since SBP is a human-made protein that has not been found in nature, the discovery of novel SBPs relied heavily on experimental protein engineering and could be greatly facilitated by in-silico studies (such as AI and computational modeling). Thus, the data provided in SYNBIP could lay a solid foundation for the future development of novel SBPs. The SYNBIP is accessible without login requirement at both official (https://idrblab.org/synbip/ ) and mirror (http://synbip.idrblab.net/ ) sites. Graphical Abstract: